Religious Liberty: Roger Williams and the Revolutionary Era - Moore, LeRoy (Church history, 1965)
The classical period for the establishment of the legal guarantees of religious freedom in America is the final quarter of the eighteenth century, otherwise known as the Revolutionary Era. Yet, enshrined in our national memory as the great hero of liberty of conscience is not a man of this classical period, but a doughty seventeenth century colonial—Roger Williams. The object of the present study is to view this hero in time and space—in that particular time remembered as the Revolutionary Era and that particular space occupied by thirteen colonies out to become a nation.